Investigating the relationship between psychological distress, posttraumatic stress disorder (PTSD), and coping strategies among hospital staff, health center staff, and the general population during the coronavirus pandemic - Abdollahpur, Mahsa; Kianimoghadam, Amir Sam; Bakhtiari, Maryam; Farahani alavi, Samira (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: The outbreak of coronavirus in Wuhan, China in 2019 has caused numerous mental health problems around the world. Among the psychological problems that have emerged due to the Covid-19 pandemic are symptoms of psychological distress, such as anxiety, depression, and PTSD disorder. The present study aimed to investigate the relationship between psychological distress, coping strategies, and PTSD among three various populations, namely the general population, hospital staff and staff of health centers during the Covid-19 pandemic. Materials and Methods: Pearson’s correlation coefficient was used to investigate the relationship between the study variables. Using convenience sampling, a sample of 450 individuals (150 participants from each population) was selected to participate in the research. Results: The findings indicated that psychological distress was significantly and negatively correlated to PTSD between two populations, i.e., the general population (r = -0.708, P < 0.01), and health center staffs (r = -0.216, P < 0.01), but coping strategies were not associated with psychological distress and PTSD in these two populations. However, the results were different among hospital staffs; in that psychological distress was significantly correlated with coping strategies (r = -0.170, P < 0.05), and PTSD (r = -0.216, P < 0.01), and there was a significant correlation between coping strategies and PTSD (r = -0.270 P < 0.01) among this population. Conclusion: These findings highlighted the need for educational courses and psychological interventions to inform different populations about various coping strategies in stressful situations, and to reduce symptoms of psychological distress during the pandemic